Disc cell senescence in intervertebral disc degeneration: Causes and molecular pathways. Issue 13 (2nd July 2016) - Feng, Chencheng; Liu, Huan; Yang, Minghui; Zhang, Yang; Huang, Bo; Zhou, Yue
ABSTRACT: The accumulation of senescent disc cells in degenerative intervertebral disc (IVD) suggests the detrimental roles of cell senescence in the pathogenesis of intervertebral disc degeneration (IDD). Disc cell senescence decreased the number of functional cells in IVD. Moreover, the senescent disc cells were supposed to accelerate the process of IDD via their aberrant paracrine effects by which senescent cells cause the senescence of neighboring cells and enhance the matrix catabolism and inflammation in IVD. Thus, anti-senescence has been proposed as a novel therapeutic target for IDD. However, the development of anti-senescence therapy is based on our understanding of the molecular mechanism of disc cell senescence. In this review, we focused on the molecular mechanism of disc cell senescence, including the causes and various molecular pathways. We found that, during the process of IDD, age-related damages together with degenerative external stimuli activated both p53-p21-Rb and p16-Rb pathways to induce disc cell senescence. Meanwhile, disc cell senescence was regulated by multiple signaling pathways, suggesting the complex regulating network of disc cell senescence. To understand the mechanism of disc cell senescence better contributes to developing the anti-senescence-based therapies for IDD.